FAST MINIMIZATION ON THE XIAO MAP USING ROW GROUP STRUCTURE RULES (Nigerian Journal of Technology, 2003)
Xiao has proposed a new graphical method suitable for the mininisation of logical functions of five or more variable. In this paper, we present a set of rules that simplify minimization using the Xiao map. We also show that the Xiao map technique compares favourable with the Quine -McCluskey algorithmic method.